Análise numérica da perda de carga localizada em escoamentos laminares de fluidos do tipo power-law e Bingham em contrações e expansões abruptas - Kfuri, Sérgio Luiz Dalvi (2010)
The calculation of head loss is essential for piping projects and selection of pumps. Of-ten the pipe lines are present accessories like bends, valves, contractions and expansions. Accesso-ries like these are responsible for a portion of the energy loss that is traditionally accounted for bythe coefficient of pressure loss located,K.The literature provides coefficients for localized head loss for Newtonian fluids forseveral geometries. Non-Newtonian materials are common in various industrial applications, butthere isn’t still complete knowledge of the head loss for the various possible geometries, and evenless for the different rheological parameters.Among the many possible manifestations for a non-newtonian fluid are pseudoplasti-city, viscoplasticity, elasticity and thixotropy there is two of interest for the proposed work: shear-thinning and viscoplasticity. The proposed work is to obtain the local loss coefficient by analy-zing the behavior of pseudoplastic and viscoplastic fluids through two typical geometries foundin pumping systems: abrupt contraction and abrupt expansion. These accessories are studied byvarying the aspect ratio.The pseudoplastic and viscoplastic is generally captured by model Generalized New-tonian fluid with use of a typical function to describe the viscosity. This paper uses the functionspower-law and Bingham. The study was conducted based on a numerical approach with the finiteelement technique with the Galerkin approximation. The results are compared with the few results xixin the literature